Особенности изготовления Cd1–xZnxTe-детектора ионизирующего излучения - Tomashik, Z. F.; Stratiichuk, I. B.; Tomashik, V. N.; Budzulyak, S. I.; Gnativ, І. І.; Komar, V. K.; Dubina, N. G.; Lots’ko , A. P.; Korbutyak, D. V.; Demchina, L. A.; Vakhnyak, N. D. (PE "Politekhperiodika", Book and Journal Publishers, 2013)
The article describes a newly-developed method of manufacturing of an operating element of the Cd1–xZnxTe-detector of ionizing radiation with high sensitivity to low-energy gamma radiation of the americium 241Am radioactive isotope. The proposed two-step method of chemical surface treatment with the use of new bromine releasing polishing etchants significantly improves the quality of the detector material and increases its specific sensitivity to ionizing radiation. This allows to use smaller Cd1–xZnxTe plates, which results in lowering of the cost of detectors.